Mortality from External Causes and Behavioral Mechanisms : An examination of data from low- and middle-income countries - Abio, Anne (fi=Turun yliopisto|en=University of Turku|, 2023)
External causes of mortality are among the leading causes of mortality, especially in low- and middle-income countries. External causes of mortality disproportionately affect youth and young adults, including those who are economically active. The aim of the following study series was to investigate trends and demographic associations of the injury-related mortality burden and suicidal behavior in low- and middle-income countries. Study I examined trends of external causes of mortality in Seychelles over a period of 30 years using civil registration data. At least three-quarters of injury deaths occurred among males. The leading causes of mortality among males was drowning, followed by road traffic injuries; and other unintentional injuries among females. The injury mortality declined over time; however, the injuries from road traffic crashes increased, especially among males. Study II analyzed trends of traumatic brain injury (TBI) related mortality in Seychelles over a span of 30 years using civil registration data. Males were more likely to die from TBI related injuries. TBIs contributed to one in five deaths from all the recorded external causes. Road traffic crashes were the leading mechanism of TBI related mortality. Study III estimated the prevalence of suicidal behavior and the associated contextual factors among adolescents in low- and middle-income countries using the Global School-based Student Health Survey data. Ten to eleven percent of adolescents had considered suicide, made a suicide plan, or attempted suicide in each case. The lowest prevalence was reported in the South East Asian region, while a higher prevalence was recorded in the low-income country regions of the Americas. The findings imply that effective policies tailored for low- and middle-income countries are required to reduce the high rates of injury mortality. Reducing injury mortality will contribute towards each respective economy by minimizing the losses of income faced by the economically active age groups, which will in turn be beneficial for the countries.

Ulkoiset kuolinsyyt ovat nuorten aikuisten merkittävimpiä kuolinsyistä matala- ja keskituloisissa maissa. Tässä väitöstutkimuksessa tutkittiin tapaturmaisten vammojen aiheuttaman kuolleisuusuuden ja itsemurhakäyttäytymisen ilmaantuvuuden muutoksia matala- ja keskituloisissa maissa. Tutkimuksessa I tutkittiin ulkoisten kuolinsyiden kehityssuuntia Seychellien tasavallassa 30 vuoden ajanjaksolla hyödyntäen väestöpohjaisia rekistereitä. Tapaturmien osuus kaikista kuolemista koko väestössä oli 8,5 %. Miesten kuolemat kattoivat lähes 3/4 kaikista tapaturmaisista kuolemantapauksista. Miehillä yleisin kuolinsyy oli hukkuminen, ja naisilla muut tahattomat vammat. Koko väestössä tapaturmaiset kuolemantapaukset vähenivät tarkasteluajanjakson aikana. Tutkimuksessa II tutkittiin tapaturmaisten aivovammojen aiheuttamien kuolemantapauksien määrien kehityssuuntia Seychellien tasavallassa 30 vuoden ajanjaksolla käyttäen väestöpohjaisia rekistereitä. Miehet kuolivat naisia todennäköisemmin aivovammoihin ja niihin liittyviin muihin vammoihin. Aivovammat aiheuttivat joka viidennen kuoleman kaikista kuolemista, joissa oli ulkoinen syy. Tieliikenneonnettomuudet olivat aivovammojen aiheuttamien kuolemien yleisin mekanismi. Tutkimuksessa III tutkittiin itsemurhakäyttäytymisen esiintyvyyttä ja siihen liittyviä tekijöitä eräiden matala- ja keskituloisten maiden nuorten keskuudessa hyödyntäen Global School Health Survey -aineistoa. 10–11 % nuorista oli harkinnut itsemurhaa, tehnyt itsemurhasuunnitelman tai yrittänyt itsemurhaa. Alhaisin esiintyvyys havaittiin Kaakkois-Aasian alueella, kun taas korkein esiintyvyys Väli- ja Etelä-Amerikan matalatuloisten maiden alueilla. Tulokset osoittavat, että matala- ja keskituloisille maille räätälöityjä käytäntöjä tarvitaan tapaturmakuolleisuuden vähentämiseksi. Tapaturmakuolleisuuden tehokas vähentäminen vähentää työikäisten ikäryhmien menetettyjä työvuosia ja tuottaa merkittäviä taloudellisia säästöjä.